Correlations of Rainfall and Forest Type with Papilionid Assemblages in Assam in Northeast India. (12th October 2010) - Barua, Kamini Kusum; Slowik, Jolanta; Bobo, Kadiri Serge; Muehlenberg, Michael
Abstract : No comprehensive community studies have been done on the butterflies of the tropical monsoon forests of the East Himalayan region. We described the Papilionidae at one site within the continuous moist deciduous forest belt of Northeast India and their variation with season and forest type. We surveyed 20 permanent line transects, varying with respect to canopy openness and observed levels of disturbance. A total sample effort of 131 days during the dry and wet seasons of a two-year study resulted in 18, 373 individuals identified from 28 Papilionidae species. Constrained canonical correspondence ordination was used to examine the effects of season, forest type, rainfall, year, altitude, and geographical position on the species assemblages. Results showed that rainfall, forest type, and season accounted for most variance in papilionid abundance. Rainfall was strongly correlated with the abundance of some species. Nine species were associated with gaps, 16 species were restricted to closed forest, and three species were encountered in both gaps and closed forest. Six species with narrow geographic range were found only in closed forest. The results confirm the strong seasonality of continental Southeast Asian butterfly assemblages.